FACTORS THAT INFLUENCE THE LEVEL OF COMPLIANCE WITH ARV IN PEOPLE WITH HIV / AIDS AT GENERAL HOSPITAL TUGUREJO AND PANTI WILASA CITARUM HOSPITAL SEMARANG - Risha Fillah Fithria; Achmad Purnomo; zullies Ikawati (Faculty of Pharmacy, Universitas Gadjah Mada)
Cases of HIV (Human Immunodeficiency Virus)/AIDS (Acquired Immune Deficiency Syndrome) in Indonesiahas increased. Overall, the city of Semarang is ranked first the number of cases of HIV/AIDS in Central Java. Anincreasing number of HIV cases is significant and increasing number of HIV sufferers turn to enter the stage ofAIDS may be caused due to poor adherence in the treatment of ARV (Anti Retro Viral). This study aims to determinethe factors that influence the level of compliance with ARV treatment significantly in people living with HIV at RSUDTugurejo Semarang and RSU Panti Wilasa Citarum Semarang. This research is a non experimental cross sectional study design. Data was collected using questionnaires,monthly drug card, and patient medical records. The data were analyzed statistically using the method of simple correlation (bivariate correlation), ie, Kendall's tau-b.Research found 34 people of respondents who have the level of compliance with ARV treatment >95%, 10people of 90-95%, and 5 people of 80-89%. Factors that influence the level of compliance with ARV treatmentsignificantly in people living with HIV at RSUD Tugurejo Semarang and RSU Panti Wilasa Citarum Semarang is afactor of patients is age (p=0.018), complaints (hallucinations, diarrhea, decreased appetite (p=0.049)), depression(p=0.049), saturated length of treatment (p=0.007), and the fear of bad outlook of people around (p=0.002), felt hishealth condition worsened (p=0.005); factor of opportunistic infection is the number of drugs taken more andmore and feel conditions are getting worse (p=0.049); resistance factor is the distance from home to hospital(p=0.001), transport equipment difficult (p=0.019), transport costs are not affordable (p=0.006); and health servicefactor is support health workers (p=0.002). Keywords: HIV/AIDS, adherence, RSUD Tugurejo, RSU Panti Wilasa Citarum